2018
DOI: 10.1001/jamasurg.2018.0974
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Institution Comparison of Resident and Faculty Perceptions of Burnout and Depression During Surgical Training

Abstract: The prevalence of burnout and depression was high among general surgery residents in this study. Attendings and residents underestimated the prevalence of these conditions but acknowledged common barriers to seeking care. Discrepancies in actual and perceived levels of burnout and depression may hinder wellness interventions. Increasing understanding of these perceptions offers an opportunity to develop practical solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 16 publications
3
60
1
1
Order By: Relevance
“…The prevalence of burnout is greater among residents than physicians or medical students of similar age [9]. Combined estimates demonstrate that burnout varies among clinical specialty from 35-84% [10][11][12][13][14][15]. And generally, burnout scores are higher in surgical and residencies requiring urgent treatment of patients [5,6].…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of burnout is greater among residents than physicians or medical students of similar age [9]. Combined estimates demonstrate that burnout varies among clinical specialty from 35-84% [10][11][12][13][14][15]. And generally, burnout scores are higher in surgical and residencies requiring urgent treatment of patients [5,6].…”
Section: Discussionmentioning
confidence: 96%
“…3 In fact, it has been asserted that more than 50% of US doctors experience burnout, a syndrome of emotional depletion and maladaptive detachment caused by prolonged occupational stress. 11 This is particularly common in residents/registrars, and even more so in those pursuing surgical disciplines. 11,12 A recent systematic review of 182 studies showed that overall physician burnout prevalence ranged from 0-80.5%, figures highly dependent on rating scales and cut-off points for burnout, and limited by nosological debate.…”
Section: Depression In Doctors: a Bitter Pill To Swallow K Outhoffmentioning
confidence: 99%
“…11 This is particularly common in residents/registrars, and even more so in those pursuing surgical disciplines. 11,12 A recent systematic review of 182 studies showed that overall physician burnout prevalence ranged from 0-80.5%, figures highly dependent on rating scales and cut-off points for burnout, and limited by nosological debate. Emotional exhaustion, depersonalization, and low personal accomplishment ranged from 0-86%, 0-90%, and 0-87%, respectively.…”
Section: Depression In Doctors: a Bitter Pill To Swallow K Outhoffmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up survey of 7,905 surgeons funded by the American College of Surgeons, Shanafelt and colleagues found that 6% reported some element of suicidal ideation during the prior 12 months, albeit only 26% sought psychiatric care for the fear of compromising their medical license [3]. Most recently, in 2018 a survey of 6 general surgery training programs in North Carolina revealed an incidence of burnout among residents and faculty of 75%, with 39% of those meeting the definition for depression [4]. A very concerning aspect of the data is that 12% reported having suicidal ideation in the prior 2 weeks.…”
mentioning
confidence: 99%